1995
DOI: 10.1007/bf00689711
|View full text |Cite
|
Sign up to set email alerts
|

Influence of n-3 fatty acids on the growth of human breast cancer cellsin vitro: Relationship to peroxides and Vitamin-E

Abstract: Epidemiological studies suggest a causal relationship of dietary polyunsaturated fatty acids (PUFA's) with the morbidity and mortality from breast cancer. In order to reveal possible underlying mechanisms of these findings, we studied the influence of n-3 and n-6 PUFA's in comparison to oleic acid on the proliferation of well characterized estrogen dependent (MCF-7, ZR-75, T-47-D) and estrogen independent (MDA-MB-231, HBL-100) breast cancer cells in culture. The cell growth inhibitory effect was related to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
124
3
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 179 publications
(141 citation statements)
references
References 30 publications
13
124
3
1
Order By: Relevance
“…[7][8][9] Several authors have reported reduced multiplication of malignant cultured cells incubated with n-3 fatty acids. 10,11 This effect has also been reported in leukemia cell lines. 12,13 Moreover, n-3 fatty acids and some other polyunsaturated fatty acids (PUFA) may decrease DNA synthesis and viability of cultured human lymphocytes.…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…[7][8][9] Several authors have reported reduced multiplication of malignant cultured cells incubated with n-3 fatty acids. 10,11 This effect has also been reported in leukemia cell lines. 12,13 Moreover, n-3 fatty acids and some other polyunsaturated fatty acids (PUFA) may decrease DNA synthesis and viability of cultured human lymphocytes.…”
Section: Introductionsupporting
confidence: 62%
“…However, the apoptosis induced by EPA in Ramos cells, was not affected by vitamin E. It has been demonstrated that the reduced cell multiplication induced by PUFA in human breast carcinoma cells and human T cells, is reversed by vitamin E and related to formation of free radicals. 11,15 However, in two very similar reports, the addition of antioxidants together with PUFA had no reversible effect. 14,16 As none of these studies investigated if the reduced cell multiplication with PUFA was caused by apoptosis or necrosis, the discrepancies in these reports may be explained by our present findings.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Les données récentes produites en culture cellulaire indiquent que les AGPI n-3, incluant l'acide alpha-linolénique, inhibent la prolifération de cellules tumorales mammaires par l'intermédiaire d'une production accrue de lipoperoxydes, et qu'une supplémentation en vitamine E, principale vitamine anti-oxydante, supprime ces effets [25]. De façon similaire, une étude utilisant un modèle animal de carcinogenèse mammaire a indiqué que l'effet inhibiteur d'apports alimentaires riches en huiles de poissons (contenant des AGPI n-3 à longue chaîne) au niveau de la croissance tumorale mammaire est aboli par une supplémentation en agents anti-oxydants [26].…”
Section: Acide Alpha-linolénique Anti-oxydants Et Croissance Tumoralunclassified
“…In response to oxidative stress, PUFAs undergo free-radical chain reaction breakdown, which results in the formation of fatty acid hydroperoxides and hydroxides as immediate products and aldehydes, among other endproducts. Either in cultured tumor cells (Chajès et al, 1996) or in tumor-bearing animals (Gonzalez et al, 1993), PUFA supplementation caused a decrease in cell proliferation or in tumor growth correlated with a concomitant increase in the level of cellular lipid peroxidation. These observations suggest that PUFAs interfere with tumor cell proliferation in vitro and in vivo due to the formation of oxidation products.…”
mentioning
confidence: 99%